Subjective Well-Being Pada Orang Dewasa Dengan HIV/AIDS (ODHA) - Triana, Ade Shasha; Dr. Wiwien Dinar Pratisti, M.Si, Psi, Dr. Wiwien Dinar Pratisti, M.Si, Psi (2017)
This study aims to determine and describe the subjective well-being of adults with HIV / AIDS (PLWHA). The approach in this study using the phenomenological qualitative methods, data analysis used was inductive data analysis is the process of collecting data using a picture story by way of abstracting after recording special phenomena grouped together. Data were collected by interview or semi-structured interviews. With the number of respondents were four adults with HIV / AIDS are aged 20-45 years. Selection of informants done by snowball sampling, to adults with HIV / AIDS are aged twenty to forty-five years. The results showed that subjective well-being in adults with HIV / AIDS, namely: 1) People with HIV / AIDS in the adult category were able to demonstrate subjective well-being indicate social relationships with good, self-acceptance, able to be grateful for what you have or obtained now, performance at work and in the community better and live a life like everyone else. While people with HIV / AIDS that subjective well-beingnya low, indicating that anxious and worried about the acceptance of the environment and feel burdened by thoughts about the condition of the body or health, 2) The support and motivation from family and neighborhood are receiving, helping people with HIV / AIDS to be able to think positive in life. So as to improve the subjective well-being of individuals, 3) The big difference in thinking between PLWHA who work with HIV and AIDS are just as housewives as well as differences between older people living with HIV have been infected with HIV / AIDS than the recently since the beginning of HIV / AIDS.